2005
DOI: 10.1590/s1413-86702005000600013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological aspects of children hospitalized with severe rotavirus-associated gastroenteritis in Salvador, BA, Brazil

Abstract: Little is known about the epidemiology of severe rotavirus-associated gastroenteritis in Brazil. Given the morbidity associated with this condition and the importance of having detailed knowledge about the impact of rotavirus infection on the epidemiology of acute diarrhea in children, especially those with the most severe diarrheal conditions, we retrospectively reviewed the medical records of all pediatric patients admitted to a tertiary hospital in Salvador, Brazil, due to rotavirusassociated gastroenteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
4
12
1
7
Order By: Relevance
“…Carneiro et al [13] demonstrated that 39% of rotavirusassociated gastroenteritis seen at the Emergency room had to be admitted to the hospital for treatment. These data reinforce the implication described of rotavirus infections with more severe cases of childhood gastroenteritis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Carneiro et al [13] demonstrated that 39% of rotavirusassociated gastroenteritis seen at the Emergency room had to be admitted to the hospital for treatment. These data reinforce the implication described of rotavirus infections with more severe cases of childhood gastroenteritis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Severely ill patients may need hospitalization and further investigation, including complete blood counts, electrolyte dosing and stool culture. Rotavirus-associated diarrhea should always be excluded in such cases, given its propensity to cause severe and dehydrating pictures [5,6]. Blood culture may also be indicated in a few cases, depending on the severity and risk of hematogenic dissemination.…”
mentioning
confidence: 99%
“…Penelitian di Bangladesh, Vietnam, Brazil, maupun negara-negara Eropa melaporkan prevalensi tertinggi diare rotavirus pada kelompok usia 6-23 bulan, kemudian menurun dengan bertambahnya umur. [4][5][6][7][13][14][15][16][17][18] Kami menemukan diare rotavirus menyerang 78,4% kasus berumur kurang dari 2 tahun dengan prevalensi tertinggi pada kelompok umur 6-23 bulan (65,5%). Anak umur 6-23 bulan rentan terkena infeksi rotavirus karena kadar antibodi ibu yang diperoleh melalui ASI mulai menurun dan mulai memasuki fase oral ketika anak suka memasukkan semua benda yang dipegang ke dalam mulut.…”
Section: Pembahasanunclassified